Counselling and group discussion - Sharma Y K (Jaipur Mark Publishers, 2022)
Job opportunities and vacancies; how prepare job applications; preparing resume for best job selection; professional courses in modern time and interview techniques group counselling and group group discussion; letter writing skills; skills and time management; skills for success; importance of english in interviews; role of personality in english speaking.
Keywords: Applied Psychology